Best of seven - Stapleton, Jonnie; Grasso, Domenico; Kelley, Paula; Armstrong, James Drew; Jester Independent (Firm); Leomark Studios (Firm) ([lugar] : Jester Independent, 2016)
A quiet man who suffers from multiple personality disorder is talked into stop taking his medications by his parents, who are sure he is fully healed. He agrees to stop taking them for a week, and that unleashes all his other personalities to destroy his life.
Originally released as a motion picture in 2016
Jonnie Stapleton, Paula Kelley, Jim Armstrong, Lacey Hannan, Pearce Joza, Sophia Flot-Warner, Erika Ishii, Michael Stephens, Myron McClure.
Cinematographer, Domenico Grasso ; music, Noah Hunt, Ryan Hobler, Lukewarm Freeda.
In English; with optional English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 20, 2017).
Keywords: Multiple personality -- Drama; Comedy films; Feature films; Internet videos; Streaming video